Implementation of a GIS-based pilot application for roads management applied to the conservation and maintenance of unpaved low traffic roads (2019)
"The lack of updating and unreliability of information has become one of the main problems that occur in the area of management of unpaved roads in developing countries as Colombia. Therefore, a GIS-based application was developed which allows keeping updated all the information at the structural and functional level of the road, and to control the premature pavement deterioration favouring the support for making decisions in management activities of the unpaved road network. In the municipality of Urrao (Antioquia), a research proposal on ""La Encarnación"" road was proposed. The Road Trial Section (RTS) is part of a bidirectional 3rd level road, which has 240 m-length and a 4 m-width. The RTS was divided into eight segments or cells (30 m-length), where each of them was stabilized with different conventional and unconventional materials (cement, hydrated lime, coal ash, brick dust, sulfonated oil, polymer and sugarcane sludge). Based on the results gathered in six pavement performance follow-up and evaluation campaigns, a geospatial database (GDB) was designed. This GDB is the core of the application ""SGVVT Urrao v1.0"" which is able to represent graphically the behaviour of the tests of functionality and the bearing capacity carried out (International Roughness Index, slip resistance, surface macro texture, lightweight deflectometer and visual inspection). The application is able to forecast the deterioration values allowing the prioritization of rehabilitation activities for the most affected sections in a given time period which is possible to extend the useful life of the roads, reduce the operation cost of the vehicles, and guarantee the road safety and the comfort of the unpaved road network users. © Published under licence by IOP Publishing Ltd."